THE LEGACY LEFT BY BOTIR ZAKIROV - Togaymurodov J. K. (European Science Publishing, 2024)
The article talks about the legacy left by Botir Zakirov.
Keywords: Botir Zakirov, youth, high morality, spirituality and enlightenment, art, science, national stage, national values